Heritage management in Korea and Japan : the politics of antiquity and identity - Pai, Hyung Il (Korean studies of the Henry M. Jackson School of International Studies., 2013)
"Imperial tombs, Buddhist architecture, palaces, and art treasures in Korea and Japan have attracted scholars, collectors, and conservators--and millions of tourists. As iconic markers of racial and cultural identity at home and abroad, they are embraced as tangible sources of immense national pride and popular "must-see" destinations.This book provides the first sustained account to highlight how the forces of modernity, nationalism, colonialism, and globalization have contributed to the birth of museums, field disciplines, tourist industries, and heritage management policies. Its chapters trace the history of explorations, preservations, and reconstructions of archaeological monuments from an interregional East Asian comparative perspective in the past century.Hyung Il Pai is professor of East Asian languages and cultural studies at the University of California, Santa Barbara. She is the author of Constructing Korean Origins."Any scholar interested in the politics of culture in imperial Japan or colonial Korea will want this book on his or her shelf." --Robert Oppenheim, University of Texas at Austin"--